(untitled) (Texas Journal of Engineering and Technology, 2022)
The article studies the process of cleaning small litter and dust during the transportation of raw cotton. A system of installations for the experimental study of the process of cleaning raw cotton from dust and small particles of litter has been developed. A regression relationship between the cleaning efficiency of raw cotton and the initial moisture content and clogging was obtained for various conveyor lengths. For the maximum and minimum lengths of the conveyor, the ranges of change in the cleaning efficiency of the installation system are determined. Based on the results of experiments and analysis of the results of their static processing, it was established that it is possible to reduce the amount of defects and contamination of hoppy fiber through the practical application of the recommended system of cleaning plants in the process of transporting raw cotton.